Urbanisation reduces litter breakdown rates and affects benthic invertebrate structure in Pampean streams. Issue 1 (23rd September 2019) - Tagliaferro, Marina; Giorgi, Adonis; Torremorell, Ana; Albariño, Ricardo
Abstract: The Pampean region has become one of the most urbanised areas in South America with more than 91% of the Argentinean population. This region is ideal for human settlements that have historically chosen riverine grassland areas to settle. Consequently, urban streams are increasingly subjected to pressures affecting their functioning. The aim of this study was to assess urbanisation effects on two proxies of stream integrity: leaf litter decay and benthic invertebrate assemblage colonizing litter in streams draining urbanised versus reference grassland areas. We placed plastic coarse‐ and fine‐mesh bags containing Populus nigra leaf litter along three urban and three reference reaches, and these were retrieved periodically to determine the remaining leaf mass and the identity and quantity of detritivore assemblage colonizing bags. The decay rate was negatively affected by urbanisation, and it followed a negative relationship with increasing Nitrogen concentration (mostly ammonia) and a hump‐shape relationship against soluble reactive phosphorus. Urban invertebrate assemblages were significantly different from the reference reaches, and were species‐poorer and characterized by tolerant taxa belonging to Naididae, Glossiphoniidae, and Nematoda, whereas Hyalellidae, Aeglidae, Chironomidae, Caenidae, Baetidae, and Hydrobiidae represented the reference reaches. Our proxies of structural (i.e., invertebrate assemblages) and functional (i.e., leaf litter breakdown) stream integrity were mostly driven by a nutrient‐enrichment gradient and responded in a similar direction but with different magnitude to urban alterations.